Glocalisation in action: 'Less is More' English coursebook series - Tuncer Can; Sarah Frazier; Colette McManus; Alex Rey (Peoples' Friendship University of Russia (RUDN University), 2020)
Globalisation has been a powerful force taking over every field for a very long time, including the field of language education. Any discussion of globalisation cannot be held in isolation without extending it to include its counterpart, localisation. Teachers of English as a foreign language have long been aware of the fact that global coursebook providers enhance global culture in their coursebooks. However, getting students to identify with these global topics within their local contexts often proves challenging. Teachers experience the frustration of mediating between the global information and the local context. As has been observed, students experience the foreignness within the lessons and shy away from exchanging ideas and practising their language skills and, thus, they cannot engage with the language work. One solution to this could be merging the two concepts of globalisation and localisation, called glocalisation. This study aims at presenting good practices of glocalisation, starting from local culture and local background awareness and extending to global topics and information. In the search to ease the teacher's mediating role and student's motivation, and embedded in global 21st century skills, our study reveals strategies to use in English coursebooks for the successful application of glocalisation in language learning with reference to ELT in particular.